Tiktok Features On Adolescent Communication Patterns: A Systematic Literature Review - Septy Nur Ramadhani (Journal Commedies, 2025)
Social media platforms like TikTok have significantly reshaped the way adolescents communicate and form their identities. Adolescence is a crucial developmental stage where communication plays a key role, and TikTok’s interactive features have increasingly influenced how teenagers express themselves and build social connections. This study aims to systematically review recent literature to examine how TikTok’s interactive features influence adolescent communication patterns. It focuses on identifying the most frequently used features by adolescents, understanding their impact on digital communication behaviors, and analyzing how these features shape routine communication in online environments. This study employed a systematic literature review following PRISMA 2009 guidelines. Literature was collected from the ScienceDirect database using the keywords “TikTok Features,” “Adolescent Communication Patterns,” and “Digital Communication.” After screening (n= 2,801) initial records and applying inclusion and exclusion criteria, (n= 10) relevant articles were selected for in-depth analysis. The study concluded that TikTok significantly influences adolescent communication patterns. Although it supports creativity and identity formation, there are risks such as compulsive use and uncritical acceptance of content. It is recommended that the platform improve transparency of its algorithms and moderation features. Further research needs to examine the impact of TikTok features more specifically on adolescent digital communication.